Preparation And Characterization Of Muscovite-Carbon Nanotubes Epoxy Layered Silicate Nanocomposites - Bakhtiar, Nur Suraya Anis Ahmad (2019)
The poor dispersion and low interfacial adhesion between carbon nanotubes (CNT) and polymer matrix are the crucial problem when incorporating of CNT in polymer nanocomposites. This work focuses on the effect of different fabrication techniques including physical mixing and chemical vapour deposition (CVD) on the mechanical and thermal conductivity properties of epoxy nanocomposites. The physically mixed muscovite MWCNT (Mus MWCNT PM) was prepared by employing the muscovite with MWCNT using ball milling for 24h at 20 rpm to examine the effect of processing on the mechanical properties of epoxy/muscovite-multiwalled carbon nanotubes. The synthesis of Mus MWCNT hybrid (Mus MWCNT HYB) filler was prepared via chemical vapour deposition (CVD) loaded nickel catalyst and muscovite as a substrate under methane flow at 800 ºC. In order to improve the dispersion of the Mus MWCNT, the muscovite clay particles were initially intercalated with lithium nitrate and followed by cetyltrimethylammonium bromide (CTAB). The modification of muscovite resulted in increased basal spacing as well as better exfoliation of the silicate layers. The organo muscovite (O-Mus) was then synthesized via CVD. The successfully synthesized Mus MWCNT and O-Mus MWCNT as well as Mus MWCNT PM were characterized using Field Emission Scanning Electron Microscopy (FESEM), High Resolution Transmission Electron Microscopy, X-Ray Diffraction (XRD), Raman Spectrum, and Fourier Transform Infrared (FTIR) before incorporated with epoxy resin. It was found that the fabrication of Mus MWCNT hybrid via CVD produce better morphological and structure compared to Mus MWCNT PM. Mus MWCNT PM, Mus MWCNT HYB and O-Mus MWCNT HYB filled epoxy were prepared by in situ polymerization and the epoxy nanocomposites system and were characterised using scanning electron microscopy (SEM) and transmission electron microscopy to evaluate the dispersibility of filler within the epoxy matrix. The Mus MWCNT HYB filled epoxy showed higher tensile, hardness, and thermal properties compared to Mus MWCNT PM filled epoxy. The high reinforcing efficiency of Mus MWCNT HYB filled epoxy nanocomposites can be attributed to the good dispersion and interfacial interaction within the epoxy matrix. The research explored the effect of organo muscovite on the properties described above of epoxy incorporated organo muscovite multiwalled carbon nanotubes (O-Mus MWCNT). The tensile and hardness properties of the O-Mus MWCNT filled epoxy nanocomposites exhibited better performance as compared to the untreated muscovite with the optimum filler loading at 3 wt%. Further, the loosely entangled O-Mus MWCNT dispersed in epoxy matrix indicated homogeneous dispersion and strong interfacial interaction between the hybrid filler and matrix, which influenced the enhancement of the mechanical properties of the epoxy nanocomposites. Therefore, it is concluded that the incorporation of O-Mus MWCNT into the epoxy matrix exhibited enhanced properties of mechanical, hardness, thermal conductivity compared to the neat epoxy, therefore satisfactorily meeting the objectives of this study.